FAKTOR-FAKTOR YANG MEMPENGARUHI KRIMINALITAS DI KABUPATEN BATANG TAHUN 2013 DENGAN ANALISIS JALUR - Dermawanti Dermawanti; Abdul Hoyyi; Agus Rusgiyono (Jurnal Gaussian, 2015)
Crime or criminality in Indonesia is rampant both in print or television can be seen almost every day news about crime. Basically, each individual will be influenced by several factors, both internal and external causes a person to commit a criminal act, including population, education, morality, poverty, and unemployment. In this case will be studied in a statistical analysis that can detect the magnitude of these factors, either directly or indirectly to the level of criminality. One of the statistical analysis that can be used to analyze the causal relationship of the variables is the path analysis (path analysis) which is a direct development of multiple regression form with the aim to provide estimates of the level of interest (magnitude) and significance (significance) in a hypothetical causal link set variable. In this study showed that the factor that has the greatest positive effect on crime is unemployment factor of 0.395 with immediate effect. A factor which has the second largest positive effect of education is a factor of 0.222 to the direct effects and the indirect effect of 0.0818. Meanwhile, a factor that has a positive influence smallest is the moral factor to the effect of 0.180.Keywords : Criminality, Path Analysis